Persepsi Muhammadiyah Sebagai Darul Ahdi Wa Syahadah - Kurniawan, Muhammad Iqbal; Muhammad Hayat (EL-TA’DIB: Journal of Islamic Education, 2025)
The concept of Darul Ahdi wa Syahadah is Muhammadiyah's ideological formulation that affirms Indonesia's position as a nation of consensus (darul ahdi) as well as a space for practicing Islamic values through the active testimony of its citizens (darus syahadah). This formulation was born from Muhammadiyah's long struggle to reconcile Islamic teachings with the realities of modern nationhood. As a progressive Islamic movement, Muhammadiyah places Pancasila as a noble national covenant that is in harmony with the values of monotheism and justice, while encouraging citizens to take on a prophetic role in development, the advancement of science, and social civility. This article discusses the theological foundations, practical implementation, and contemporary challenges in realizing Darul Ahdi wa Syahadah as a paradigm of moderate Islamic nationalism in Indonesia.